2020
DOI: 10.1186/s40981-020-00400-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided inferior alveolar nerve block for trismus during dental treatment: a case report

Abstract: Background Temporomandibular disorder (TMD) is a broad term that encompasses pain and/or dysfunction of the masticatory musculature and TM joints (TMJs). When TMD becomes a chronic condition, the symptoms are extremely difficult to manage and require multiple interventions. Case presentation A woman in her 50s developed TMD after a traffic accident 30 years ago. The patient presented with severe trismus due to TMJ pain and a maximum mouth opening of 20 mm. Ultrasound-guided inferior alveolar nerve block (IANB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Ultrasound-guided inferior alveolar nerve block (UGIANB) approaches the same area as the conventional IANB from the body surface. In recent years, it has shown high success rates and effectiveness in mandible surgery [ 11 , 12 ]. UGIANB is useful because it allows real-time monitoring of the needle tip, the important structures such as the arteries and the muscles, and the local anesthetic.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound-guided inferior alveolar nerve block (UGIANB) approaches the same area as the conventional IANB from the body surface. In recent years, it has shown high success rates and effectiveness in mandible surgery [ 11 , 12 ]. UGIANB is useful because it allows real-time monitoring of the needle tip, the important structures such as the arteries and the muscles, and the local anesthetic.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown that ultrasound-guided TNB provides good post-operative analgesia in maxillofacial surgeries [2][3][4][5][6][7][8][9]. Additionally, ultrasound-guided TNB can be performed under general or local anesthesia without complication [10]. Here, we report the results of our use of this technique via the case of a patient with dental phobia.…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor, Recent studies have reported that ultrasound-guided trigeminal nerve blocks are effective as a postoperative analgesic method in maxillofacial surgery [1][2][3][4]. These mainly include ultrasound-guided inferior alveolar nerve blocks (IANBs), also called mandibular nerve blocks, and ultrasound-guided maxillary nerve blocks (MNBs) [5].…”
mentioning
confidence: 99%